Validation of a Monte Carlo tool for patient-specific dose simulations in multi-slice computed tomography. - Deak P; van Straten M; Shrimpton PC; Zankl M; Kalender WA; Deak, Paul; van Straten, Marcel; Shrimpton, Paul C; Zankl, Maria; Kalender, Willi A (European Radiology, 2008)
Estimating the dose delivered to the patient in X-ray computed tomography (CT) examinations is not a trivial task. Monte Carlo (MC) methods appear to be the method of choice to assess the 3D dose distribution. The purpose of this work was to extend an existing MC-based tool to account for arbitrary scanners and scan protocols such as multi-slice CT (MSCT) scanners and to validate the tool in homogeneous and heterogeneous phantoms. The tool was validated by measurements on MSCT scanners for different scan protocols under known conditions. Quantitative CT Dose Index (CTDI) measurements were performed in cylindrical CTDI phantoms and in anthropomorphic thorax phantoms of various sizes; dose profiles were measured with thermoluminescent dosimeters (TLD) in the CTDI phantoms and compared with the computed dose profiles. The in-plane dose distributions were simulated and compared with TLD measurements in an Alderson-Rando phantom. The calculated dose values were generally within 10% of measurements for all phantoms and all investigated conditions. Three-dimensional dose distributions can be accurately calculated with the MC tool for arbitrary scanners and protocols including tube current modulation schemes. The use of the tool has meanwhile also been extended to further scanners and to flat-detector CT.